2007
DOI: 10.1016/j.envpol.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

New exposure-based metric approach for evaluating O3 risk to North American aspen forests

Abstract: A new exposure-based metric approach to predict O 3 risk to North American aspen forests has been developed. AbstractThe United States and Canada currently use exposure-based metrics to protect vegetation from O 3 . Using 5 years (1999e2003) of comeasured O 3 , meteorology and growth response, we have developed exposure-based regression models that predict Populus tremuloides growth change within the North American ambient air quality context. The models comprised growing season fourth-highest daily maximum 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…There are many investigations in the literature indicating that plants may acclimate over time to added CO 2 (Kö rner, 2006), but this does not appear to be so for O 3 . The effects of O 3 found in the present study are generally consistent with previously reported reductions in overall growth under added O 3 at the site and the improved relative performance of the O 3 -resistant aspen clone 8L in the presence of added O 3 Percy et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are many investigations in the literature indicating that plants may acclimate over time to added CO 2 (Kö rner, 2006), but this does not appear to be so for O 3 . The effects of O 3 found in the present study are generally consistent with previously reported reductions in overall growth under added O 3 at the site and the improved relative performance of the O 3 -resistant aspen clone 8L in the presence of added O 3 Percy et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…The decreases attributed to elevated O 3 are consistent with the generally observed reduction of growth. The increases other than that for branch magnitude were probably due to the increased relative performance of relatively O 3 -tolerant clones in the presence of competition with less O 3 tolerant genotypes, although Percy et al (2007) mentions the possibility of hormetic O 3 effects.…”
Section: Discussionmentioning
confidence: 98%
“…Current and projected [O 3 ] are sufficient to cause chronic changes in trees [for reviews see Chappelka & Samuelson (1998); Skarby et al (1998); Karnosky et al (2007); Matyssek et al (2007)], most notably reductions in photosynthesis (Long & Naidu, 2002; Wittig et al , 2007), accelerated leaf senescence (Pell et al , 1999; Karnosky et al , 2005; Nunn et al , 2005) and decreased productivity (Percy et al , 2007). Forests are one of the most important global sinks for carbon (Geider et al , 2001; Houghton, 2003; Sitch et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that the rise in [O 3 ] since the Industrial Revolution has already resulted in a significant decrease in tree leaf photosynthesis (Wittig et al , 2007), but does this translate into a loss in biomass and production? Percy et al (2007) estimated a maximum 31% loss in productivity of Populus tremuloides in parts of its North American range between 2001 and 2003 due to O 3 . How widespread are such decreases and can we assess whether there has been an overall loss and by what amount?…”
Section: Introductionmentioning
confidence: 99%
“…The authors were careful to note that none of the O 3 parameters examined showed a statistically significant relationship to growth and should not be used alone to predict growth [24]. Percy et al [25] combined the fourth highest 8-h average concentration experienced in their high exposure chambers with other parameters and found a statistically significant result. It is important to note that those study conclusions were derived with data from fumigation exposures with high hourly average concentrations in the experimental chambers and the 8-h average concentrations may be highly correlated with the frequent occurrences of these elevated levels.…”
Section: Critical Loads/levels In the Us And Canadamentioning
confidence: 99%